Meditation and interoception: a conceptual framework for the narrative and experiential self - Gibson, Jonathan Earl (Frontiers in Psychology, 2024)
The concept of the self is complex and there is no consensus on what the self is. However, there are emerging patterns in the literature that point to two different selves, the narrative and experiential self. The narrative self refers to a conceptual or representational knowledge of the self that extends across time and manifests in self-reflection and personality assessments. The experiential self refers to firstperson perception, moment-to-moment awareness, embodiment, and a sense of agency. These two selves are reliably linked to two distinct neural circuits, the default mode network (DMN) and the insula and salience network (SN). One of the consistent themes in the meditative and mindfulness literature is a change in the perspective of the self. In this paper, I will review how meditation alters those neural circuits providing a plausible mechanism that can explain the changes in the self. I also propose a rudimentary conceptual framework to account for some of the mixed results found throughout meditation literature. personality assessments (McCrae & Costa, 1997). The "I" or experiential self refers to first-person perception, moment-to-moment awareness, embodiment, and a sense of agency (Farb et al., 2007; Seth, 2013;Monti et al., 2022;Nave et al., 2021). In short, the narrative self is the part of the self that can be observed or described (e.g., outgoing, friendly etc.) while the experiential self eludes observation and description because it is the part of the self that is doing the observing and describing.Recent studies have begun to reliably identify distinct neural circuits associated with these different selves. The Narrative or "me" self has been consistently linked to the default mode network (DMN) (